Idiosyncratic Behavior of Shareholders Toward Corporate Sustainability Reports - Singh, Amit Kumar; Kumar Goel, Sandeep (Prabandhan: Indian Journal of Management, 2023)
Purpose : The present study focused on identifying the factors influencing shareholders’ perception toward corporate sustainability reports. The growing importance of climate-sensitive activities in response to global warming induced us to find out the importance of sustainability reports in the minds of shareholders.x Methodology : Seven independent latent variables, namely message characteristics, manager characteristics, assurance and accountability, standards and ratings, intra-firm factors, corporate governance mechanisms, and challenges and risks, were undertaken in the study. Further, the perception of the shareholders measured along the parameter of importance was taken as the dependent variable. For the study, we floated a structured questionnaire, received 412 responses, and ran the analysis on SMART PLS. Findings : We found that only four variables out of seven significantly influenced the perception of the shareholders toward corporate sustainability reports. To elaborate, message characteristics, assurance and accountability, and corporate governance mechanisms positively influenced the perception of the shareholders, while standards and ratings negatively influenced the perception of the shareholders. Practical Implications : It was recommended that corporations must publish credible, accurate, and adequate information while inviting active participation from the shareholders. Our study is not free from limitations and allows scope for future researchers – whether differences in the perception of the shareholders arising due to various boundaries could be undertaken in future research work. Originality : Unlike prior research on corporate social responsibility, the current work builds a model to examine shareholders’ perceptions toward corporate sustainability reports.